(untitled)
A simple empirical relation is proposed to correlate the K-hindrance factor with the number of quasiparticles in the state configuration. The reduced hindrance F_ u = (t_1/2^γ /t_1/2^w )^1/ u has been empirically modified such that u= Δ K-L-(N_π-N_ u), instead of ormalsize u = Δ K-L where N_ u and ormalsize N_π are the numbers of neutron and proton quasiparticles in the state configuration. In systematics, the modified hindrance factor can be used to uniquely determine the K-isomer state configuration., number=2, journal=Письма в ЭЧАЯ, year=2024, month=May